Risk Factors of Diarrhoea among Children Under Five Years in Southwest Nigeria - Harriet U. Ugboko; Obinna C. Nwinyi; Solomon U. Oranusi; Fasina F. Fagbeminiyi (International Journal of Microbiology)
Diarrhoea is the passage of three or more loose or liquid stools per day or more frequent passage than is normal for an individual. Diarrhoea alters the microbiome, thus the immune system, and is a significant cause of morbidity and mortality in young children. This study evaluated the association between the risk factors and diarrhoea prevalence among children under five years in Lagos and Ogun States, located in Southwest Nigeria. Participants included 280 women aged 15–49 years and children aged 0–59 months. The study used quantitative data, which were assessed by a structured questionnaire. Data obtained were analyzed using the Statistical Package for the Social Sciences Software Version 25.0 and Microsoft Excel 2013. The relationships and/or association between variables were evaluated using Pearson's Chi Square and logistic regression tests. One hundred and eighteen (42%) of the children were male, and 162 (58%) were female. The majority of the children belonged to the age group 0–11 months (166). Age (p=0.113) and gender (p=0.366) showed no significant association with diarrhoea among the children. The majority of the mothers belonged to the age group 30–34. Multivariate analysis showed that the mother's level of education (95% CI for OR = 11.45; P=0.0001) and family income (95% CI for OR = 7.61, P=0.0001) were the most significant risk factors for diarrhoea among children. Mother’s educational status, mother's employment, and family income were the factors significantly associated with diarrhoea in Southwest Nigeria. The study recommends that female education should be encouraged by the right government policy to enhance the achievement of the sustainable development goal three (SDG 3) for the possible reduction of neonates and infants' deaths in Nigeria.